FAKTOR YANG MEMENGARUHI KELUARGA DALAM KEPEMILIKAN SARANA BUANG AIR BESAR DI DESA JANJIMANAON KECAMATAN BATANG ANGKOLA KABUPATEN TAPANULI SELATAN TAHUN 2017 - Habibah, Nursalmah; Rangkuti, Juni Andriani (Universitas Aufa Royhan, 2018)
The environment is a major factor that affect the health of individuals and communities. Environmental conditions that do not meet the requirements of health and social behavior can be detrimental to health of both rural and urban communities due to lack of knowledge and keamampuan community health, economics, and technology. The purpose of this study to determine the factors that affect the ownership healthy latrine in the village Promise Manaon district. Angkola Batang district. South Tapanuli 2017. This type of research is analytic survey with cross sectional approach, which aims to analyze the factors that affect families in a healthy latrine ownership family in the village of Promise Manaon Angkola District of South Tapanuli. The population in this study is a household that has a healthy latrines in the village of Promise Manaon district. Angkola Batang district. South Tapanuli as many as 88 households. The sampling technique in this research is total sampling as many as 88 respondents. Data obtained from questionnaires and were analyzed using chi square test and multiple linear regression. showed that the results of the test-F or simultaneous test known to have the effect of independent variables (economic status, knowledge, attitude, clean water and the role of health workers) to the dependent variable (latrine ownership) in the village of Janjimanaon District of Batang Angkola South Tapanuli Year 2017.It that the most dominant variable influence on the family in a village latrine ownership in the District of Batang Angkola Janjimanaon South Tapanuli Year 2017 is a variable of knowledge with significant value 0.006 <0.05. It is expected that all healthcare workers to be able to provide health promotion in order to increase knowledge with regard to the ownership healthy latrine for the community in the village of Batang Angkola Janjimanaon District of South Tapanuli.